Health system adaptations and considerations to facilitate optimal oral pre-exposure prophylaxis scale-up in sub-Saharan Africa. Issue 8 (August 2021) - Were, Daniel K; Musau, Abednego; Atkins, Kaitlyn; Shrestha, Prakriti; Reed, Jason; Curran, Kelly; Mohan, Diwakar
Summary: Following WHO's 2015 recommendation, countries in sub-Saharan Africa have progressively scaled up oral pre-exposure prophylaxis (PrEP) as part of combination HIV prevention. PrEP has potential to significantly reduce new HIV infections in sub-Saharan Africa if it is widely available, accessible, and effectively used. Initial scale-up efforts have generated progress, drawing lessons from existing HIV interventions, such as antiretroviral therapy and biomedical prevention. However, beset by unprepared health systems, scale-up has been slow, resulting in suboptimal coverage among priority groups at higher risk of HIV acqusition. Using the WHO health system building blocks framework, this Review synthesises literature on essential considerations for PrEP scale-up in sub-Saharan Africa, highlighting the importance of health system adaptability and responsiveness.